Islam di Layar Kaca Global: Studi Komparatif Narasi Dakwah Televisi di Indonesia dan Mesir - Abiyyu, Livyo Faiq; Khasanah, Eva Lutfiati; Saefulloh, Aris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the dynamics of Islamic broadcasting in the digital era through a comparative analysis of Islamic television in Indonesia and Egypt. Using a qualitative approach based on literature review and media content analysis, the research highlights how socio-political variables, media regulations, and religious authority shape da'wah strategies, broadcast narratives, and responses to digital disruption in both countries. The findings reveal that in Indonesia, a relatively open democratic climate and the diversity of religious actors have encouraged the emergence of Islamic television that is communicative, innovative, and responsive to digital media. In contrast, in Egypt, Islamic broadcasting operates within a more centralized system tightly controlled by the state and official religious institutions, tending to maintain conservative broadcasting patterns despite beginning to adopt digital formats. This comparison underscores that Islamic broadcasting is not merely a religious phenomenon, but also a reflection of the configuration of power and media policies in each country. This study contributes conceptually to the understanding of the relationship between digital da'wah, media politics, and cross-cultural religious configurations.